The Analysis of Performance Based on Balanced Scorecard at Karangasem Hospital - Putu Yulianti; I Nyoman Sutarsa; I Putu Ganda Wijaya (Public Health and Preventive Medicine Archive, 2016)
Background and purpose: Karangasem Hospital has adopted balanced scorecard method in preparation of the strategic plan. The performance evaluation has been done based on accountability report only with the three other perspectives have never been analysed before. This study was conducted to assess those four perspectives. Methods: Cross-sectional survey was carried out among 110 inpatients and 95 employees which were selected conveniently. The data were collected by interviews using questionnaire. The data were analyzed with kartesius graph to get each item of patients and employees satisfaction that need to be priority. Secondary data analysis conducted to know the tendency of those four perspectives. Results: Based on the assessment of the four perspectives showed that the overall score is 44.7%. It is defined as sufficient category. This also can be observed that each perspective of finance, customers and internal business process included in sufficient category. Their scores are 16.65%, 12.5% and 15.62%. Meanwhile, for the learning and growth perspective showed as weak category (0). Kartesius graph analysis showed that two items of patient’s satisfaction have to do with procedure and quick service need to be concerned. However, the employees’ satisfaction showed that there are five sub items which need to be concerned. They are quick response, management support and working environment. Conclusion: The performance of Karangasem Hospital based on scorecard is in the sufficient category and patients/employee’s satisfaction still need to be concerned on certain items.